Development of Kosbarab Learning Media to Improve Arabic Vocabulary Mastery of Elementary Level Students Based on Android Construct 2 - Rifda Amalia; Muhammad Afthon Ulin Nuha; Afif Kholisun Nashoih (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2022)
In this current metaverse era, Arabic learning containing mufradat has not applied construct 2 media in the learning process so far. When viewed from the media, it will certainly match to the current metaverse era, and its application is also accessible. This study aims to design an Arabic vocabulary learning medium and to determine the feasibility of developing an android-based KOSBARAB learning medium to be applied in Arabic subject for 5D MI Bahrul' Ulum Tambakberas Jombang students. The research method used is Research and Development (R&D) with a development model from Borg and Gall, which consists of 10 stages. Research instruments include observation, interviews, questionnaires, and trials. Data from experts